1994
DOI: 10.1007/bf01974603
|View full text |Cite
|
Sign up to set email alerts
|

Randomized comparative trial with ampicillin/sulbactam versus cefamandole in the therapy of community acquired pneumonia

Abstract: In a randomized prospective study ampicillin/sulbactam and cefamandole were compared in the therapy of patients hospitalized with community acquired pneumonia. Patients receiving ampicillin/sulbactam (n = 37) and cefamandole (n = 38) were similar with respect to age (mean age 70 vs. 76 years respectively), clinical characteristics, severity of illness and underlying disease. Pathogens isolated from patients in the cefamandole and ampicillin/sulbactam group, respectively, were Streptococcus pneumoniae (7 vs. 7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 28 publications
0
11
0
1
Order By: Relevance
“…The literature review for the period 1981–2008 provided only 19 acceptable articles relevant to the antibiotic management of CAP 277 364 365 366 367 368 369 370 371 372 373 374 375 376 377 378 379 380 381 . [Ib] [Ib] [Ib] [Ib] [II] [Ib] [Ib] [Ib] [Ib] [Ib] [Ib] [Ib] [Ib] [Ib] [Ib] [Ib] [Ib] [Ib] [Ib] The remainder were rejected for the following reasons: inadequately powered studies or a retrospective design,102 382 383 384 385 386 387 388 389 390 391 392 393 394 395 396 397 398 399 400 non-blinded/non-randomised studies,274 401 402 403 404 405 antibiotic not available in the UK or withdrawn,357 361 406 407 408 409 410 411 412 413 414 415 416 417 418 419 420 421 422 423 424 425 426 427 428 429 430 431 432 433 434 435 436 437 438 439 440 441 study population or management unrepresentative of normal clinical practice in the UK,377 442 …”
Section: Section 8 Antibiotic Managementmentioning
confidence: 99%
“…The literature review for the period 1981–2008 provided only 19 acceptable articles relevant to the antibiotic management of CAP 277 364 365 366 367 368 369 370 371 372 373 374 375 376 377 378 379 380 381 . [Ib] [Ib] [Ib] [Ib] [II] [Ib] [Ib] [Ib] [Ib] [Ib] [Ib] [Ib] [Ib] [Ib] [Ib] [Ib] [Ib] [Ib] [Ib] The remainder were rejected for the following reasons: inadequately powered studies or a retrospective design,102 382 383 384 385 386 387 388 389 390 391 392 393 394 395 396 397 398 399 400 non-blinded/non-randomised studies,274 401 402 403 404 405 antibiotic not available in the UK or withdrawn,357 361 406 407 408 409 410 411 412 413 414 415 416 417 418 419 420 421 422 423 424 425 426 427 428 429 430 431 432 433 434 435 436 437 438 439 440 441 study population or management unrepresentative of normal clinical practice in the UK,377 442 …”
Section: Section 8 Antibiotic Managementmentioning
confidence: 99%
“…However, H. parainfluenzae is increasingly recognized as a pathogen in respiratory tract infections. Williams et al (28) found that H. parainfluenzae was the second-most prevalent organism isolated from their patients. Poirier (26) found H. parainfluenzae to be a target pathogen in his study of CAP patients being treated with clarithromycin or roxithromycin.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies, however, have shown that other pathogens have become increasingly more significant (1,2,5,12,20). These include Haemophilus influenzae (15), Moraxella catarrhalis (10), Staphylococcus aureus (20), Haemophilus parainfluenzae (28), aerobic gram-negative bacilli (20), and viruses (3) as well as Legionella, Chlamydia, and Mycoplasma (10). However, in as many as 49 to 60% of the cases, the microbial etiology of the disease remains uncertain (3,10).…”
mentioning
confidence: 99%
“…Durante este período, los índices de resistencia de Klebsiella pneumoniae al espectro extendido de las cefalosporinas disminuyó signifi cativamente desde 62 a 42% 163 . Es de notar que los estudios que evalúan la efi cacia y seguridad de ampicilina/ sulbactam parenteral son escasos e incluyen un número limitado de pacientes 164 . Sin embargo, ampicilina/sulbactam se está utilizando en cierto grado en E.U.A.…”
Section: Grupo 2 (Crb-65: 1-3 Pacientes Hospitalizados En Sala Generunclassified